Penerapan Regulasi Hukum Terhadap Kasus Pungutan Liar oleh Penyelenggara Parkir Ilegal di Kota Surabaya - Rohmah, Muhimmatur; Fauzi, Agus Machfud (Universitas Muhammadiyah Yogyakarta, 2024)
Population growth in Indonesia affects the number of private transportation owned by people in Indonesia. The tendency of Indonesian people to choose to use private transportation is what causes the increasing number of vehicles in Indonesia. Of course, if transportation ownership increases, the need for parking lots will also increase. In big cities, for example Surabaya, parking problems have been rampant and even flourished. Unscrupulous individuals who take advantage of the provision of parking lots have emerged, especially in places of commerce and also tourist attractions. In Surabaya City, regulations have actually been issued regarding the implementation of parking in Surabaya City, namely Surabaya City Regulation No. 3 of 2018. However, in its implementation it has not yet been implemented in accordance with existing regulations. This study aims to provide benefits to the community and government to be wiser in responding to the problem of extortion by illegal parking organizers and to create a better and more orderly city environment. Qualitative research methods are used in this study and using data sourced from literature studies. This study also uses symbolic interaction theory and structural functional theory. Both theories are used to examine how legal regulations can influence behavior, norms, and relationships between individuals in society. The results of this study explain that public perception of illegal parking and the legal regulations applied are still pros and cons. Some people consider illegal parking to be normal, but some people also consider illegal parking to be quite disturbing. The less than optimal implementation of legal regulations also encourages the proliferation of illegal parking in Ketintang Village, Surabaya City.